If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -6 + 5x + 3 = 46 Reorder the terms: -6 + 3 + 2x + 5x = 46 Combine like terms: -6 + 3 = -3 -3 + 2x + 5x = 46 Combine like terms: 2x + 5x = 7x -3 + 7x = 46 Solving -3 + 7x = 46 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 7x = 46 + 3 Combine like terms: -3 + 3 = 0 0 + 7x = 46 + 3 7x = 46 + 3 Combine like terms: 46 + 3 = 49 7x = 49 Divide each side by '7'. x = 7 Simplifying x = 7
| A(3x+8)=-18x+b | | 40x=41x-2 | | 3x+17=4x | | -c=-22 | | 3+1=4x+1 | | 3x^3-5x^2+10x+9= | | q-11=9 | | 33x+-4=95 | | 3+1=7y+2 | | 2w+3-4w=17-(3w+2) | | 3+1=7y-2 | | 3=-12c+7 | | 3+1=7y-9 | | 15t-11t= | | 3=-15/2 | | 4x+4+4x=2(4x+2) | | 3/5=f/-5 | | 3/5=f-5/5 | | 13m+m= | | 7Y+25=56 | | 5(x+2)+x=6(x+3)-4x | | -4/7y=-8 | | 3x^3+6x^2-24x+15=0 | | x^1/2-8x^1/4-15=0 | | -2r-r-8=5r-12 | | 6w-8+4w= | | 8-2(x+1)+3x=12 | | w+9x=4ax | | (3a+26)+(5a-4)= | | -1/6=5 | | 14-3n=n-1 | | 3(4x-3)=8x-33 |